Pengaruh Implementasi Kebijakan E-Government dan Tata Kelola Pemerintah Terhadap Kinerja Pegawai pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Garut - Wulan Hervina Destriana; Yogi Suprayogi Sugandi; Ginanjar Wira Saputra (Journal Of Administration and Educational Management (ALIGNMENT), 2023)
This research aims to determine the effect of implementing E-Government policies on team member performance, the impact of government governance on team member performance, and the effect of implementing E-Government policies and government governance on the performance of Garut district population and civil registration service employees. This research method is quantitative. With a population of 54 people, the total number of employees is the Garut Regency Population and Civil Registration Service. The research sampling method uses a saturated sample method so that the number of samples is the same as the total population. Data analysis uses multiple linear regression analysis. The research results show that implementing e-government policies and government governance partially and simultaneously influences team member performance, with a contribution of 72.6%. In conclusion, there is a significant influence between the implementation of E-Government Government Governance policies on team member performance. Keywords: Implementation of E-Government Policy, Employee Performance, Government Governance